Glomerular hyperfiltration and hypertrophy: an evaluation of maximum values in pathological indicators to discriminate “diseased” from “normal” - Kataoka, Hiroshi; Nitta, Kosaku; Hoshino, Junichi (Frontiers in Medicine, 2023)
The success of sodium-glucose cotransporter 2 inhibitors and bariatric surgery in patients with chronic kidney disease has highlighted the importance of glomerular hyperfiltration and hypertrophy in the progression of kidney disease. Sustained glomerular hyperfiltration and hypertrophy can lead to glomerular injury and progressive kidney damage. This article explores the relationship between obesity and chronic kidney disease, focusing on the roles of glomerular hyperfiltration and hypertrophy as hallmarks of obesity-related kidney disease. The pathological mechanisms underlying this association include adipose tissue inflammation, dyslipidemia, insulin resistance, chronic systemic inflammation, oxidative stress, and overactivation of the sympathetic nervous system, as well as the renin-angiotensin aldosterone system. This article explains how glomerular hyperfiltration results from increased renal blood flow and intraglomerular hypertension, inducing mechanical stress on the filtration barrier and post-filtration structures. Injured glomeruli increase in size before sclerosing and collapsing. Therefore, using extreme values, such as the maximal glomerular diameter, could improve the understanding of the data distribution and allow for better kidney failure predictions. This review provides important insights into the mechanisms underlying glomerular hyperfiltration and hypertrophy and highlights the need for further research using glomerular size, including maximum glomerular profile, calculated using needle biopsy specimens.